Adaptive resilient control design for nonlinear time‐delay systems against unknown state‐dependent deception attacks. (12th December 2021) - Song, Shuai; Zhang, Baoyong; Park, Ju H.; Song, Xiaona
Abstract: This article investigates the adaptive resilient control problem for a class of nonlinear time‐delay systems (TDSs) with unknown state‐dependent deception attacks. For the purpose of overcoming the issue of "explosion of complexity" existing in the traditional backstepping control design and improving filter performance, an improved fractional‐order command filtered backstepping technique is adopted to obtain the filtered signals of the virtual control laws. Furthermore, the corresponding auxiliary system and attack compensator are constructed to compensate the effects of input delay and unknown sensor deception attacks. Stability results prove that all the signals in the closed‐loop systems are semi‐globally uniformly ultimately bounded (SGUUB) by using the proposed adaptive resilient controller. Finally, two simulation examples are provided to show the effectiveness of the developed control method.